Peginterferon alfa-2a plus ribavirin for treating chronic hepatitis C virus infection: Analysis of Mexican patients included in a multicenter international clinical trial - Bosques Padilla, Francisco Javier; Trejo Estrada, Rafael; Campollo Rivas, Octaivio; Cortez Hernández, Carlos Alejandro; Dehesa Violante, Margarita; Maldonado Garza, Héctor Jesús; Pérez Gómez, Héctor Raúl; Cabrera Valdespino, Armando (2003)
Treatment with polyethylene glycol-modified interferon alfa-2a (peginterferon) alone produces significantly higher sustained antiviral responses than treatment with interferon alfa-2a alone in patients with chronic hepatitis C virus (HCV) infection. We compared the efficacy and safety of peginterferon alfa-2a plus rib-avirin, interferon alfa-2b plus ribavirin, and peginterferon alfa-2a alone in the initial treatment of chronic hepatitis C. Thirty-two patients were randomly assigned to treatment, and received at least one dose of medication consisting of 180 μ of peginterferon alfa-2a once weekly plus daily ribavirin (1,000 or 1,200 mg, depending on body weight) (n = 14), weekly peginterferon alfa-2a plus daily placebo (n = 6), or three million units of interferon alfa-2b thrice weekly plus daily ribavirin for 48 weeks (n = 12). More patients who received peginterferon alfa-2a plus ribavirin had a sustained virologic response (defined as the absence of detectable HCV RNA 24 weeks after cessation of therapy) than patients who received interferon alfa-2b plus ribavirin (7/14 vs. 4/12) or peginterferon alfa-2a plus placebo (0/6). The overall safety profiles of the three treatment regimens were similar. In conclusion, for patients with chronic hepatitis C, once-weekly peginterferon alfa-2a plus ribavirin was tolerated as well as interferon alfa-2b plus ribavirin and produced significant improvements in the rate of sustained viral reduction compared with interferon alfa-2b plus ribavirin or peginterferon alfa-2a alone.